INTEROGASI W.S. RENDRA TERHADAP PEMBANGUNAN INDUSTRI ERA PEMERINTAH ORDE BARU: KAJIAN TRANSDISIPLINER - Salamah, Umi; Rokhyanto, Rokhyanto (Diksi, 2020)
(Title: Interogation W.S. Rendra on Industry Development in the Government of The New Orde Age: A Transdiciplinary Study). W.S. Rendra is a Man of letters whom always interesting to be studied from social science disciplines, because most of his works are created from the results of his research on socio politics in his era. His critical strength, his spirit of  nationalism and his courage make his works to be the spirit of rising new awareness for organic intellectuals to fight against dehumanization of his nation. The New Order Government was a system of government that did not allow of a second choices. In the name of state stabilities, everything was commanded from the top to down. The questions were considered hostile to the state and have legal consequences. This strategy occurs in every policy. This article was taken from part of the results of research from the works of W.S. Rendra who interogated the concept and realization of development was implemented  by the New Order Government. This study uses the analysis of transdisipliner theory with a designing of  critical discourse's Michel Foucault. The analysis of this article explain how industrial development 5.0 should be carried out for the Indonesian economic independence and the prosperity of the people. Keywords: Interrogation, Society 5.0, New Order Government, transdisipliner studies